EU FP7 research funding for an orphan drug (Orfadin®) and vaccine (Hep C) development: a success and a failure? - L. Schmidt; O. Sehic; C. Wild (Taylor & Francis Group, 2021)
Background We considered the extent of the contribution of publicly funded research to the late-stage clinical development of pharmaceuticals and medicinal products, based on the European Commission (EC) FP7 research funding programme. Using two EC FP7-HEALTH case study examples-representing two types of outcomes-we then estimated wider public and charitable research funding contributions. Methods Using the publicly available database of FP7-HEALTH funded projects, we identified awards relating to late-stage clinical development according to the systematic application of inclusion and exclusion criteria, classified them according to product type and clinical indication, and calculated total EC funding amounts. We then identified two case studies representing extreme outcomes: failure to proceed with the product (hepatitis C vaccine) and successful market authorisation (Orfadin® for alkaptonuria). Total public and philanthropic research funding contributions to these products were then estimated using publicly available information on funding. Results 12.3% (120/977) of all EC FP7-HEALTH awards related to the funding of late-stage clinical research, totalling € 686,871,399. Pharmaceutical products and vaccines together accounted for 84% of these late-stage clinical development research awards and 70% of its funding. The hepatitis C vaccine received total European Community (FP7 and its predecessor, EC Framework VI) funding of €13,183,813; total public and charitable research funding for this product development was estimated at € 77,060,102. The industry sponsor does not consider further development of this product viable; this now represents public risk investment. FP7 funding for the late-stage development of Orfadin® for alkaptonuria was so important that the trials it funded formed the basis for market authorisation, but it is not clear whether the price of the treatment (over €20,000 per patient per year) adequately reflects the substantial public funding contribution. Conclusions Public and charitable research funding plays an essential role, not just in early stage basic research, but also in the late-stage clinical development of products prior to market authorisation. In addition, it provides risk capital for failed products. Within this context, we consider further discussions about a public return on investment and its reflection in pricing policies and decisions justified.